SARS-CoV-2 Mediated Endothelial Dysfunction: The Potential Role of Chronic Oxidative Stress - Chang, Ryan; Mamun, Abrar; Dominic, Abishai; Le, Nhat-Tu (Frontiers in Physiology, 2021)
Endothelial cells have emerged as key players in SARS-CoV-2 infection and COVID-19 inflammatory pathologies. Dysfunctional endothelial cells can promote chronic inflammation and disease processes like thrombosis, atherosclerosis, and lung injury. In endothelial cells, mitochondria regulate these inflammatory pathways via redox signaling, which is primarily achieved through mitochondrial reactive oxygen species (mtROS). Excess mtROS causes oxidative stress that can initiate and exacerbate senescence, a state that promotes inflammation and chronic endothelial dysfunction. Oxidative stress can also activate feedback loops that perpetuate mitochondrial dysfunction, mtROS overproduction, and inflammation. In this review, we provide an overview of phenotypes mediated by mtROS in endothelial cells – such as mitochondrial dysfunction, inflammation, and senescence – as well as how these chronic states may be initiated by SARS-CoV-2 infection of endothelial cells. We also propose that SARS-CoV-2 activates mtROS-mediated feedback loops that cause long-term changes in host redox status and endothelial function, promoting cardiovascular disease and lung injury after recovery from COVID-19. Finally, we discuss the implications of these proposed pathways on long-term vascular health and potential treatments to address these chronic conditions.